The ZupT transporter plays an important role in zinc homeostasis and contributes to Salmonella enterica virulence - Cerasi, Mauro (2014)
Zinc is an essential metal for cellular homeostasis and function in both eukaryotes and prokaryotes. To acquire this essential nutrient, bacteria employ transporters characterized by different affinity for the metal. Several studies have investigated the role of the high affinity transporter ZnuABC in the bacterial response to zinc shortage, showing that this transporter has a key role in adapting bacteria to zinc starvation. In contrast, the role of the low affinity zinc importer ZupT has been the object of limited investigations. Here we show that a Salmonella strain lacking ZupT is impaired in its ability to grow in metal devoid environments and that a znuABC zupT strain exhibits a severe growth defect in zinc devoid media, is hypersensitive to oxidative stress and contains reduced level of intracellular free zinc. Moreover, we show that ZupT plays a role also in the ability of S. Typhimurim to colonize the host tissues. During systemic infections, the single zupT mutant strain was attenuated only in Nramp1(+/+) mice, but competition experiments between znuABC and znuABC zupT mutants revealed that ZupT contributes to metal uptake in vivo independently from the presence a functional Nramp1 transporter. Altogether, the here reported results show that ZupT plays an important role in Salmonella zinc homeostasis, being involved in metal import both in vitro and in infected animals.